Обсяг предмета правового регулювання у кримінальному процесі - Лоскутов, Тимур Олександрович; Лоскутов, Тимур Александрович; Loskutov, Timur (Одеса : Юрид. л-ра, 2012)
Article is devoted to study the volume of the subject of legal regulation in the criminal process. Proved that the volume of the subject of legal regulation of the CPC in the regulation of the European human rights standards is narrowed.
Лоскутов Т. О. Обсяг предмета правового регулювання у кримінальному процесі / Т. О. Лоскутов // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 706-714.
Keywords: обсяг предмета правового регулювання; права і законні інтереси людини; європейські стандарти дотримання прав людини; объем предмета правового регулирования; права и законные интересы человека; европейские стандарты соблюдения прав человека; volume of the subject of legal regulation; rights and lawful interests of man; European standards of human rights